(untitled) (Research, Society and Development, 2025)
The aim of this article is to report the results of the training experience lived by medical students at the Unichristus University Center. The aim was to identify problem situations with establish priorities using epidemiological criteria in Primary Health Care Units (UAPS) in the municipality of Fortaleza. This project was divided into three stages. Firstly, a Primary Health Care Management Workshop was held with professionals from the Municipal Health Department, teachers and students. Among the issues raised by the working groups, one of the most prevalent was Low Adherence to Prenatal Care. In the second stage, under the guidance of the UAPS preceptors, it was decided that the intervention activities would take place with the Community Health Agents (ACSs). A form was drawn up to identify and solve the problems encountered at the UAPS. In addition, a class on prenatal care, pregnancy and contraception was held for the ACSs. Finally, was talked to the management team of the Unit about the health indicators of the equipment in question and the demands of users, as well as the services provided by the multi-professional team and the results achieved. In the final stage of the activity, the results of the interventions were discussed at a meeting at the Faculty. It is possible to say that, in addition to the rich learning from the four months of care at the UAPS, taking part in this training experience has enabled a greater appropriation of knowledge relating to the National Primary Care Policy, seeking to identify demands and plan interventional actions in health, with reference to local and national indicators.